Extreme Asia the rise of cult cinema from the Far East - Martin, Daniel (Edinburgh University Press, 2015)
How shrewd marketing engineered the East Asian cult film boom in the UK. Japanese horror. South Korean revenge thrillers. The new Hong Kong crime film. Western audiences have experienced a boom in cult cinema from East Asia over the last decade, discovering films that have provoked passion and outrage in equal measure. This book charts the history of the recent cult Asian film invasion, covering a five-year period and focusing on the activities of the distribution company Metro-Tartan and their incredibly influential 'Asia Extreme' brand. Through a series of case studies of individual film releases and other exhibition events, Extreme Asia examines strategies of film promotion and consumption in the context of theories of horror cinema, movie marketing, reception studies, and Orientalism. It covers the rise and fall of the Asia Extreme label, and the enduring legacy of an unforgettable wave of cult cinema from Japan, Hong Kong, and South Korea